EVALUATION OF THE EFFECTIVENESS OF MICROSURGICAL VARICOCELECTOMY IN INFERTILE PATIENTS AT 19-8 HOSPITAL, MINISTRY OF PUBLIC SECURITY (Vietnam Journal of Community Medicine, 2026)
Objectives: Our study aimed to evaluate the effectiveness of microsurgical varicocelectomy in treating male infertility.Subjects and methods: Data were collected retrospectively from 55 cases of infertile men with clinical varicocele who underwent microsurgical varicocelectomy from December 2021 to December 2025 at the Department of Urology, 19-8 Hospital, Ministry of Public Security. Patients were followed-up 3 months, 6 months and 9 months using semen analysis and hormonal tests.Results: Mean age of patients was 29.09 ± 2.72 years. Primary infertility was found in 83.6% of patients and the prevalence of secondary infertility was 16.4%. Symptom improvement has been reported in most of patients after the surgical. The sperm analysis revealed statistically significant increases in sperm concentration, progressive sperm motility and normal morphology (p < 0.05). The adjusted testosterone levels increased in hypogonadism group. Reported pregnancy rates was 54.6%, besides the rate of spontaneous pregnacy was 43.6%.Conclusions: Microsurgical varicocelectomy is an effective procedure for the treatment of varicocele, especially in patients who were infertility. This can improve semen parameters and increase spontaneous pregnacy rates.
Keywords: Varicocele, microsurgical varicocelectomy, semen analysis, testosterone, male infertility.